Vulnerability and threat: describing gay male victimologies in South Africa by analysing online community reports - Van Der Schyff, Marchant (Frontiers in Sociology, 2025)
This study examines the phenomenon of violence towards gay men in South Africa, focusing on its portrayal and understanding within online media. Using a qualitative approach, it explores how online reports construct, interpret, and contest narratives surrounding these attacks. The investigation aims to highlight the portrayal of the victimology of gay men and the societal dynamics, including gender-based violence, abduction, victimisation, and queercide, in the South African context. The research analysed online reports, between 2022 and 2024, by a community organisation on cases of violence perpetrated against gay men. The research found that media frames about the circumstances of violence, the role of social media or hookup apps, and demographic details of gay men can provide insights into their victimhood. This contributes to the understanding of the challenges gay men face in navigating their identities and safety in South Africa. The findings show that Gauteng, Cape Town, and Durban remain the most affected by attacks against gay men and provide more insight into the strata of the age of victims, their movement, and the nature of attacks. By identifying how online community media frames these cases, the study offers insights into the emergence of gangsterism and the use of mobile technologies to target these men. It can inform strategies for social change and foster inclusive environments for marginalised communities. The findings have implications for advocacy, policy making, and community empowerment efforts addressing queercide and promoting LGBTIQ+ rights and safety.